PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD PADA BANK PERKREDITAN RAKYAT DI KOTA KUPANG - Cecilia Wirna F. Rowa; I Komang Arthana (Universitas Nusa Cendana, 2019)
The purpose of this study was to determine the effect of the principles of good corporate governance on fraud prevention in Rural Banks in Kupang City, East Nusa Tenggara Province. This research was conducted on five Rural Credit Banks out of a total of seven Rural Credit Banks in Kupang City. Rural Banks in East Nusa Tenggara Province experienced business growth with relatively stable financial performance The testing methods used are descriptive statistics, inferential statistics consisting of assessment of the measurement model / outer model and assessment of the structural model / inner model and hypothesis testing.The results of this study show that the principles of good corporate governance have a positive and significant effect on the prevention of fraud in Rural Banks in the City of Kupang.